THE EFFECT OF PREDICT OBSERVE EXPLAIN LEARNING MODEL AGAINST SCIENCE PROCESS SKILLS OF HIGH SCHOOL STUDENTS - Ayu Novitasari Pane; I Dewa Putu Nyeneng; I wayan Distrik (Universitas Tanjungpura, 2020)
This study was aimed to determine the effect of POE learning model on science process skills of high school students in the material of Newton’s Law motion. The study might benefit to a provide different learning experience that makes students become more active in learning and to improve students' science process skills towards the material being taught. The populations in this study were all students of class IPA X of SMA 5 Bandar Lampung in the even semester of the Academic Year 2018/2019, consisting of 6 classes with a total of 203 students, with samples of class X IPA 1 as the experimental class and X IPA 2 as the control class. Research method of the study was quasi-experimental. The research used a pretest-posttest control group design. The result of the study revealed that the control class using the conventional learning model had an average N-gain of 0.42, while the experimental class using the POE learning model had an average N-gain of 0.72. The effect size in this study, which was 0.71, indicated that the POE learning model has a high effect in this study. Based on the hypothesis test, it can be concluded that there was an effect of applying the POE learning model to students' science process skills in the material of Newton's Law. The magnitude of the influence of the POE learning model was classified into the high category with the Cohen’s d value of 3.40 and the effect size r of 0.71.